Pemasangan Lampu Jalan sebagai Upaya Peningkatan Keamanan dan Aksesibilitas di Padukuhan Keruk II - Gian Heman Sigalingging; Kevin Alexander; Wulandari, Kristina (Jurnal Atma Inovasia, 2026)
The KKN program implemented in Padukuhan Keruk II aims to improve the quality of street lighting infrastructure through the installation of Public Street Lighting (PJU). The lack of lighting at several strategic points has negatively affected the safety, comfort, and socio-economic activities of the local community. The program involved observing the hamlet’s conditions, determining appropriate locations for street lights, and carrying out the installation process. The implementation of this program included the installation of LED lights at two main locations selected based on community needs. The results show that the presence of PJU not only improves visibility but also reduces the potential for accidents and crime. Furthermore, the activities carried out have the potential to encourage the growth of nighttime economic activities and strengthen social interactions among residents in Padukuhan Keruk II.